2012
DOI: 10.1016/j.cgh.2011.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, Comorbidities, and Management of Irritable Bowel Syndrome in Patients in a Large Health Maintenance Organization

Abstract: Background Irritable bowel syndrome (IBS) imposes significant clinical and economic burdens. We aimed to characterize patterns of practice for patients with IBS who were members of a large health maintenance organization, analyzing point of diagnosis, testing, comorbidities and treatment. Methods Members of Kaiser Permanente Northern California who were diagnosed with IBS were matched to controls by age, sex, and period of enrollment. We compared rates of testing, comorbidities and interventions. Results F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 49 publications
4
74
2
Order By: Relevance
“…Although the exact role of anxiety and depression in the pathophysiology of IBS is currently unknown, both have been associated with increased risk for IBS. Indeed, anxiety and depression occurred in a significantly greater number of patients with IBS compared with individuals without IBS (p < 0.0001 for both anxiety and depression) [Koloski et al 2012;Ladabaum et al 2012]. Further, 38% of patients with IBS have reported thoughts of suicide and, although rare, some patients with IBS have also attempted suicide (5%) [Miller et al 2004].…”
Section: Pathophysiology Of Ibsmentioning
confidence: 99%
“…Although the exact role of anxiety and depression in the pathophysiology of IBS is currently unknown, both have been associated with increased risk for IBS. Indeed, anxiety and depression occurred in a significantly greater number of patients with IBS compared with individuals without IBS (p < 0.0001 for both anxiety and depression) [Koloski et al 2012;Ladabaum et al 2012]. Further, 38% of patients with IBS have reported thoughts of suicide and, although rare, some patients with IBS have also attempted suicide (5%) [Miller et al 2004].…”
Section: Pathophysiology Of Ibsmentioning
confidence: 99%
“…Furthermore, approximately half of the patients recalled having these symptoms when admitted, yet records revealed that few had been suspected by their physicians to have IBS [30]. Misdiagnosis of various abdominal and pelvic diseases in patients with IBS is reflected by unnecessary surgery, especially cholecystectomy, appendectomy, and hysterectomy [19,31,32].…”
Section: Discussionmentioning
confidence: 96%
“…The symptom-based somatic and mental disorders assessed have special relevance to the misattribution of IBS symptoms to diverticulitis because they tend to cluster and occur more often in patients with IBS than controls [16,19]. Importantly, high levels of these comorbid conditions are thought to reflect general amplification of symptom reporting and physician consultation rather than unique associations [16].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations